﻿New record of Pterois cf. miles (Actinopterygii: Scorpaeniformes: Scorpaenidae) from the eastern middle Adriatic Sea (Croatian waters): Northward expansion - Branko Dragičević (Pensoft Publishers, 2021)
A single specimen of Pterois cf. miles has been recorded in the eastern middle Adriatic Sea. It was observed near the island of Vis at a depth of 15 m. The location of the record is further north than previous Adriatic records and it constitutes the northernmost record of this species in the Mediterranean Sea to date. The record is based solely on photographs and video footage provided by a professional underwater photographer.